Brassinosteroids: Molecular and physiological responses in plant growth and abiotic stresses - Hafeez, Muhammad Bilal; Zahra, Noreen; Zahra, Kiran; Raza, Ali; Batool, Aaliya; Shaukat, Kanval; Khan, Shahbaz (Plant stress (Amsterdam), 2021)
lBrassinosteroids are involved in the advancement of plant growth and development.lBrassinosteroids improves crop yields by altering plant metabolism and protecting plants from several abiotic stresses.lBrassinosteroids regulate gene expression and signal transduction pathways to stimulate abiotic stress tolerance. Abiotic stresses are major constrain in agriculture development, which results in a significant decline in crop productivity. Conferring abiotic stress in plants is relatively a complex process, and diverse mechanisms are being explored recently; however, the use of phytohormones in ameliorating the abiotic stress gained considerable interest. Plants adapt to various environmental stresses by changing physiological and molecular processes, which are cooperatively modulated with the changing level of external and internal phytohormones, including brassinosteroids (BRs). BRs are the steroidal phytohormones, best known for their role in plant growth and development for the last two decades. The molecular and physiological aspects of BRs under stress condition has resulted in a better understanding. The intrinsic mechanisms concerning these processes are still elusive. This mini-review explored the role of BR in singling cascades and regulating physiological processes such as photosynthesis, nutrient metabolism, water status, hormonal cross-talk at the molecular level, and positive role in plant growth and abiotic stress tolerance. [Display omitted] .